Dataset associated with "Effects of fuel moisture content on emissions from a rocket-elbow cookstove" - van Zyl, Lizette; Tryner, Jessica; Bilsback, Kelsey; Good, Nicholas; Hecobian, Arsineh; Sullivan, Amy P.; Zhou, Yong; Peel, Jennifer; Volckens, John (Colorado State University. Libraries, 2019)
Exposure to air pollution from solid-fuel cookstoves is a leading risk factor for premature death; however, the effect of fuel moisture content on air pollutant emissions from solid-fuel cookstoves remains poorly constrained. The objective of this work was to characterize emissions from a rocket-elbow cookstove burning wood at three different moisture levels (5%, 15%, and 25% on a dry mass basis). Emissions of CO2, carbon monoxide (CO), methane, formaldehyde, acetaldehyde, benzene, toluene, ethylbenzene, xylenes, fine particulate matter (PM2.5), elemental carbon (EC), and organic carbon (OC) were measured. Emission factors (EFs; g·MJdelivered-1) for all pollutants, except CO2 and EC, increased with increasing fuel moisture content: CO EFs increased by 84%, benzene EFs increased by 82%, PM2.5 EFs increased by 149%, and formaldehyde EFs increased by 216%. Both modified combustion efficiency and the temperature at the combustion chamber exit decreased with increasing fuel moisture, suggesting that the energy required to vaporize water in the fuel led to lower temperatures in the combustion chamber and lower gas-phase oxidation rates. These results illustrate that changes in fuel equilibrium moisture content could cause EFs for pollutants such as PM2.5 and formaldehyde to vary by a factor of two or more across different geographic regions.
This dataset includes cookstove emissions data per energy delivered and per mass of fuel burned. Emissions data on a per-energy-delivered basis have units of grams per megajoule delivered. Emissions data on a per-mass-of-fuel-burned basis have units of grams per kilogram of fuel. These data were collected in a laboratory cookstoves testing facility at Colorado State University. The data file includes the following columns: 1. test_id - test ID (used internally to identify test replicates), 2. date - date on which the test replicate was conducted, 3. stove - name of the stove model tested, 4. fuel - name of the fuel, 5. fuel_shape - shape of the fuel, either "Milled" or "Split", 6. mc_level - moisture level of the fuel, either "Low", "Medium", or "High", 7. fuel_mc_dry - the moisture content of the fuel on a dry mass basis, in percent, 8. pollutant - name of the pollutant, 9. value - value of the emissions metric, 10. units - units associated with the emission metric, either "g_MJd" or "g_pol_kg_fuel".
Department of Mechanical Engineering
Department of Environmental and Radiological Health Sciences
Department of Atmospheric Science
Keywords: combustion; air pollution; wood smoke; particulate matter; formaldehyde; benzene